A new species of large carpenter bee, Xylocopa (Hymenoptera: Apidae), from Argentina - Lucía, Mariano (2010)
The new species Xylocopa (Neoxylocopa) atamisquensis is described and illustrated from adult female and male specimens. We designate Predio Isla Verde (28°38′54″S, 64°04′58″W; 120 m), Department Atamisqui in south-central Santiago del Estero province, Argentina, as the type locality. The closest species are X. (N.) mendozana and X. (N.) ordinaria.